Impact of aided AAC interventions on speech comprehension of children with neurodevelopmental disabilities: A critically appraised topic. Issue 1 (3rd April 2019) - Elmquist, Marianne; Simacek, Jessica; Dimian, Adele F.; Reichle, Joe
Abstract: A critically appraised topic (CAT) is one form of rapid review that can be particularly useful for informing practice. The purpose of this CAT was twofold: to determine (a) the impact of aided augmentative and alternative communication interventions on speech and graphic symbol comprehension in children, aged birth-18 years with neurodevelopmental disabilities and (b) whether there are any potential learner characteristics that serve as moderators or mediators regarding intervention outcomes. In addition to the methodology, the authors present and discuss the findings of this CAT. The authors propose an update to this CAT in January 2022.